Same educational level, same wage returns? An analysis over time and across occupations in Germany - Friedrich, Anett [Verfasser]; Hirtz, Sandra [Verfasser] (My University, 2021)
"Analysing wage differentials due to educational investments within occupations can explain the persistent wage inequality in western industrialised countries, such as Germany. This article contributes to the discussion by examining occupation-specific variance in wage returns for men working full-time in Western Germany between 1976 and 2010. We distinguish between three groups: employees with a vocational education and training (VET) degree with an Abitur (a certificate allowing entrance into a German university), with a VET degree but no Abitur, or with a university degree. First, we theoretically argue why wage returns vary within educational levels across occupations. Second, on the assumption that wage return variance will be greater at higher educational levels, we investigate wage return variance patterns for VET and university graduates over time. Estimating a two-stage multilevel model using the Sample of Integrated Labour Market Biographies (SIAB), we show that holding an Abitur increases wage return variance across occupations. Moreover, we find a significantly higher occupation-specific variance in wage returns to education for university graduates than for VET graduates. For the period under examination, we reveal a fluctuating variance in wage returns for VET graduates and a slightly decreasing variance for university graduates." (Author's abstract ; BIBB-Doku)
Keywords: G 1.3.3.1 Qualifikationsverwertung; S 4.1 Finanzierungsquellen; T 3.5 Statistik; 370; Bildungsökonomie; Schulabschluss; Abitur; Berufsabschluss; Studienabschluss; Bildungsertrag; Einkommen; Bildungsinvestition; Varianzanalyse; 1976-2010